2005
DOI: 10.3171/jns.2005.102.6.1142
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged perivascular spaces mimicking multicystic brain tumors

Abstract: The authors present two cases in which enlarged Virchow-Robin spaces were located in the basal ganglia and the thalamomesencephalic region. The incidence of such huge cystic lesions is extremely rare. The expanding nature of these lesions, demonstrated by the patients' progressive symptoms due to compression of the adjacent brain parenchyma and obstructive hydrocephalus, mimicked that of brain tumors. The two patients were successfully treated by neuroendoscopic cystocisternostomy or ventriculocystostomy. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 14 publications
0
50
0
Order By: Relevance
“…They associated ETV with cyst wall biopsy, observing radiological and clinical improvement of the headache and right arm and leg weakness. Rohlfs et al described two cases of enlarged perivascular spaces of the basal ganglia-thalamo-mesencephalic region successfully treated with the endoscope [4]. In both cases the cysts were opened, one into the third ventricle, the other into the interpeduncular cistern, with resolution of the clinical disturbances in both (hemihypesthesia and tremor of the left hand respectively).…”
Section: Casementioning
confidence: 95%
See 4 more Smart Citations
“…They associated ETV with cyst wall biopsy, observing radiological and clinical improvement of the headache and right arm and leg weakness. Rohlfs et al described two cases of enlarged perivascular spaces of the basal ganglia-thalamo-mesencephalic region successfully treated with the endoscope [4]. In both cases the cysts were opened, one into the third ventricle, the other into the interpeduncular cistern, with resolution of the clinical disturbances in both (hemihypesthesia and tremor of the left hand respectively).…”
Section: Casementioning
confidence: 95%
“…Ventriculo-peritoneal (V-P) shunting has been used with obvious relief of the clinical signs of hydrocephalus [10,19], but leaves the cyst intact, with the midbrain compressive syndrome being treated medically with limited effects. Rohlfs and colleagues also agreed that placement of a CSF shunt or ETV were treatment options for hydrocephalus, but these procedures do not improve the focal symptoms nor arrest growth of the cystic lesion [4]. They also concluded that ventriculo-cystostomy or cyst-cisternostomy is needed to effectively treat cysts causing brainstem compression.…”
Section: Casementioning
confidence: 96%
See 3 more Smart Citations